ANALISA MANFAAT EKONOMI DAN PERAN LEMBAGA PETANI TAMBAK (Studi Deskriptif di Desa Ambeng-ambeng Watang rejo Kecamatan Duduk Sampeyan Kabupaten Gresik) - Winarto; M. Husni Tamrin (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2017)
Fishery aquaculture activities become the core livelihood in some communities in rural areas. This study describes the value of economic benefits and the role of pond farming institutions in the community that became the needs and daily livelihoods. This research observes how the value of economic benefits and how the role of pond farming institutions in the Village of Ambeng-ambeng Watangrejo Duduk Sampeyan District Gresik.The results of this study conclude that the economic benefit value for the farmers is not profitable and even a loss. The role of farmer groups that have not yet had a good function. Group "Usaha Tani" is still not maximized in performing its role as economic institution of the community in the village Ambeng-ambeng Watangrejo Duduk Sampeyan District Gresik. Three indicators that they can play are the guidance of exchange of goods / barter, the guidance of how to pay, and as the identity of the community. But there are three other indicators that they have not done in their role as economic institutions that is as a guideline to determine food prices, buying and selling guidelines and use labor guidelines.